Numerical Modelling-Based Stability Analysis of Waste Dump Slope Structures in Open-Pit Mines-A Review - Gupta G.; Sharma S.K.; Singh G.S.P.; Kishore N. (My University, 2025)
The depths of open-pit mines have been increasing in the last few decades. This transformation generates a vast amount of waste rock material per unit mining area imposing a significant economic, social and environmental liability on the mine operators. The scarcity of dumping land along with the rise in population, competing urbanization and associated environmental clearance problems require accommodating this ever-growing volume of waste rock material at restricted available space. On the contrary, the frequency of accidents due to the instability of the waste dump slope structures has also increased, resulting in significant fatalities, apart from the economic, social and environmental impacts of these disasters. Numerous scientific studies have been conducted to reduce the occurrence of such incidents. This paper conducts a critical review of the numerical modelling-based stability analysis of such waste dump slope structures. The popularly cited cases of dump slope instability have been analysed to synthesize pertinent findings regarding the approach of stability analysis, broader design criteria, and optimization. The critical parameters to numerical modelling-based design of a safe dump slope structure are discussed in detail. The significant output parameters, apart from the factor of safety, are also outlined for evaluating the state of stability. © 2021, The Institution of Engineers (India).